• Предмет: Математика
  • Автор: Аноним
  • Вопрос задан 5 лет назад

пожалуйста с пошаговым объяснением

Приложения:

Ответы

Ответ дал: suleimandariya
1

Пошаговое объяснение:

 -  \frac{11}{5}  + 3 \frac{1}{3}  -  \frac{7}{5}  + 3 \frac{2}{3}   +  2 \frac{1}{5}  =  -  \frac{11}{5}  +  \frac{10}{3}  -  \frac{7}{5}  +  \frac{11}{3}  +  \frac{11}{5}  =  -  \frac{33}{15}  +  \frac{50}{15}  -  \frac{21}{15}  +  \frac{55}{15}  +  \frac{33}{15 }  =  \frac{50}{15}  -  \frac{21}{15}  +  \frac{55}{15}  =  \frac{84}{15}  =  \frac{28}{5}  = 5 \frac{3}{5}


Аноним: спасибо огромное
Похожие вопросы